2021
DOI: 10.3390/molecules26226915
|View full text |Cite
|
Sign up to set email alerts
|

In-Vitro Screenings for Biological and Antioxidant Activities of Water Extract from Theobroma cacao L. Pod Husk: Potential Utilization in Foods

Abstract: Increasing production of cocoa (Theobroma cacao L.) leads to a higher environmental burden due to its solid waste generation. Cocoa pod husk, one of the major solid wastes of cocoa production, contains rich bioactive compounds unveiling its valorization potential. With that in mind, our research aimed to explore the biological and antioxidant activities of aqueous extracts from cocoa pod husks. In this present work, cocoa pod husk was extracted using water and subsequentially partitioned using n-hexane, ethyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 51 publications
(79 reference statements)
0
18
1
1
Order By: Relevance
“…This value is lower in comparison to that obtained from our previous study using aqueous extraction, where the highest antioxidant was IC 50 =9.61 μg/mL and the highest cytotoxicity -74 LC 50 =μg/mL. 10 However, more cytotoxically active compounds were obtained in the n-hexane extract of T. cacao pod husk with LC 50 as low as 0.29 μg/mL. 9 The bioactivities of T. cacao pod husk could be associated with the phenolic compound contained in the extract as suggested previously.…”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations
“…This value is lower in comparison to that obtained from our previous study using aqueous extraction, where the highest antioxidant was IC 50 =9.61 μg/mL and the highest cytotoxicity -74 LC 50 =μg/mL. 10 However, more cytotoxically active compounds were obtained in the n-hexane extract of T. cacao pod husk with LC 50 as low as 0.29 μg/mL. 9 The bioactivities of T. cacao pod husk could be associated with the phenolic compound contained in the extract as suggested previously.…”
Section: Discussioncontrasting
confidence: 69%
“…9 The bioactivities of T. cacao pod husk could be associated with the phenolic compound contained in the extract as suggested previously. 10 Further purification of fraction TCEA 6 in this present study produced 4 subfractions (TCEA6.1-6.4), with TCEA 6.3 being the most predominated with polyphenol (based on FeCl 3 5% test). The GC-MS analysis on subfraction TCEA 6.3 revealed its phytoconsituents consisted of bioactive compounds lupeol, syringaresinol, catechol, and squalene among many other compounds.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The highest total phenolic content was found in the ethyl acetate fraction (9.1000 ± 0.1414), followed by the acetone fraction (6.1300 ± 0.0707), and the lowest in the methanol extract (4.4950 ± 0.3046). Yahya et al [11] reported that the total phenolic content of the ethyl acetate fraction was 570.44 mg/g GAE. The total phenolic content of husk can vary between samples depending on soil conditions, the environment, solvents used, and extraction methods [12].…”
Section: Total Phenolic Contentmentioning
confidence: 99%
“…The total phenolic content of husk can vary between samples depending on soil conditions, the environment, solvents used, and extraction methods [12]. Soil, air, and environmental conditions can influence the physical and chemical content of the samples [11].…”
Section: Total Phenolic Contentmentioning
confidence: 99%